Promoting Rural Education: The Role of the Society of the Provision of Education in Rural Australia (SPERA) - Boylan, Colin (Australian and International Journal of Rural Education, 2012)
The paper explores the role of the Society for the Provision of Education in Rural Australia (SPERA) and the challenges it has faced as the primary voice for Australian rural educators. The paper charts the origins of SPERA, and the contributions of key people involved in its foundation. The paper then examines the advocacy and impact of SPERA through its initiatives in establishing an internationally recognised national conference, the creation of Australia‟s only specifically rural education journal, Education in Rural Australia and the recognition of exceptional rural education institutions through its Australia Rural Education Award program.